Saved by the Lifeboat - Ballantyne, R. M. (Robert Michael), 1825-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"Saved by the Lifeboat" by R. M. Ballantyne is a novel written in the mid-19th century. The story centers around a seaside village facing shipwrecks and the importance of a lifeboat service, highlighting the courageous efforts of the local community to save lives from the treacherous sea. The central characters include Captain Boyns, who is determined to ensure the safety of those at sea, and John Webster, a shipowner who undergoes a personal transformation. At the start of the book, readers are introduced to a harrowing storm that has caused a shipwreck off the coast of a village named Covelly. Captain Boyns, after sensing the urgent need for a lifeboat, rushes out into the storm with his son Harry to rescue those in danger. As the local men rally to launch the lifeboat amidst the violent waves, they face immense challenges and dangers. The opening also establishes tensions related to John Webster, a shipowner whose negligence leads to disaster, but he ultimately experiences a change of heart after being directly affected by the wreck of his ship, the "Water Lily", and the rescue efforts that unfold. This setup emphasizes the themes of bravery, community service, and moral responsibility. (This is an automatically generated summary.)
Release date is 2007-11-06
Produced by Nick Hodson of London, England
Keywords: Shipwrecks -- Juvenile fiction; Royal National Life-Boat Institution for the Preservation of Life from Shipwreck (Great Britain) -- Juvenile fiction; Ships -- Safety regulations -- Juvenile fiction; Lifeboats -- Juvenile fiction; Search and rescue operations -- Juvenile fiction